2014
DOI: 10.5935/1984-6835.20140066
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted acid Digestion Procedure for Trace Elements Determination in PolychaeteChaetopterus variopedatus

Abstract: Procedimento de Digestão Assistido por Micro-ondas para Determinação de Elementos-traços no Poliqueta Chaetopterus variopedatusResumo: Este estudo avaliou e aplicou uma digestão, com ácido diluído, assistida por micro-ondas para determinar elementos-traço (As, Ba, Cd, Co, Cr, Cu, Hg, Mn, Ni e Sb) em amostras de poliquetas (Chaetopterus variopedatus). Após a otimização do método, empregando-se material certificado de referência (1566b CRM, tecido Oyster), os analitos foram determinados por espectrometria de mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…For instance, Yang et al reported recoveries of Na, Al, K, V, Co, Zn, Se, Sr, Ag, Cd, Ni, and Pb between 90–110% determined by ICP-MS. 33 In another microwave-assisted acid digestion procedure for determination of metal contents in marine invertebrates, recoveries of 85% and 110% were reported for Cu and Ba, respectively. 34 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Yang et al reported recoveries of Na, Al, K, V, Co, Zn, Se, Sr, Ag, Cd, Ni, and Pb between 90–110% determined by ICP-MS. 33 In another microwave-assisted acid digestion procedure for determination of metal contents in marine invertebrates, recoveries of 85% and 110% were reported for Cu and Ba, respectively. 34 …”
Section: Resultsmentioning
confidence: 99%
“…For instance, Yang et al reported recoveries of Na, Al, K, V, Co, Zn, Se, Sr, Ag, Cd, Ni, and Pb between 90-110% determined by ICP-MS. 33 In another microwaveassisted acid digestion procedure for determination of metal contents in marine invertebrates, recoveries of 85% and 110% were reported for Cu and Ba, respectively. 34 Low (1 ppb) and high (45 ppb) platinum quality control samples were used for assessing the freeze-thaw, shortterm stability, and long-term stability of the test samples in both rat urine and rat liver matrices. Results suggested that the samples were stable after three cycles of freezethaw and after short-and long-term storage for up to three months (Supplemental Material, Tables 6S-8S).…”
Section: Resultsmentioning
confidence: 99%